Adaptation strategies for climate change impacts on water quality: a systematic review of the literature. Issue 3 (26th December 2022) - Bartlett, Jenelle A.; Dedekorkut-Howes, Ayşın
Abstract: Climate change will impact water bodies and create significant challenges for natural resource managers. Despite the increasing impacts of climate change on water quality, the development and implementation of long-term strategic adaptation measures are seldom governmental priorities. So far, research has mainly tended to focus on the availability and volume of water rather than the quality. Comparatively fewer studies have considered adaptation strategies that deal with the uncertainties of the impacts of climate change on the quality of water bodies. This paper reports the results of a systematic review of literature on adaptation options and the barriers and drivers that can exert a positive or negative influence on their implementation. Findings suggest that there has been and continues to be a cautious approach to a growing concern for a natural resource of utmost necessity. Most of the strategies mentioned in the literature use coping or incremental approaches. However, adaptation strategies offering low levels of resilience for addressing water quality may not be up to the challenge of significant future climate changes. HIGHLIGHTS: The impacts of climate change on water quality are increasing at an alarming rate. Still, most research is focusing on impacts on water supply, disregarding water quality. Similarly, there is an emphasis on adaptation strategies that address water security, with much fewer addressing water quality. Many of the adaptation strategies for water quality use coping or incremental approaches with scant evidence of transformational adaptation.